Direct Spectrophotometric Determination of Vanadium with 3-hydroxy-3-phenyl-1-p-carboxyphenyltriazene - Rezaie, Behrooz; Goswami, A.K.; Purohit, D.N. (Asian Journal of Chemistry, 2010)
3-Hydroxy-3-phenyl-1-p-carboxyphenyltriazene was used for spectrophotometric determination of vanadium. The composition of the yellowish green complex is 1 : 1 (V : R) with maximum absorbance at 395 nm and working wavelength was chosen to be 420 nm using solvent as blank. Molar absorptivity and Sandell's sensitivity were found to be 9550 l/mole cm and 5.33 ng/cm2 respectively in the pH range 6.5 to 7.0. Beer's law was obeyed in the range 0.50 to 3.05 ppm of vanadium. Standard deviation 'σ' (10 determinations) using 2.54 ppm of vanadium was 0.002. Interference of 22 diverse ions was studied.